2016
DOI: 10.1371/journal.pone.0164966
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Subset Progression and Polyfunctionality of T Cells in Mice Exposed to Methamphetamine during Chronic LCMV Infection

Abstract: Methamphetamine (METH) is a widely used psychostimulant that severely impacts the host’s innate and adaptive immune systems and has profound immunological implications. T cells play a critical role in orchestrating immune responses. We have shown recently how chronic exposure to METH affects T cell activation using a murine model of lymphocytic choriomeningitis virus (LCMV) infection. Using the TriCOM (trinary state combinations) feature of GemStone™ to study the polyfunctionality of T cells, we have analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…In this regard, our earlier study has shown that exposure of T cells to METH results in the loss of T-cell proliferative activity 15 . Of relevance are our recent findings in a murine model that suggests, METH-induced microenvironment results in upregulation of immunoinhibitory programmed cell death-1 (PD-1) marker, alters homeostatic proliferation and differentiation pathways of T-cell subsets in an animal model of chronic viral infection 20 , 21 . In this present study, we explored the effect of METH on cell cycle regulators and their role in suppression of T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our earlier study has shown that exposure of T cells to METH results in the loss of T-cell proliferative activity 15 . Of relevance are our recent findings in a murine model that suggests, METH-induced microenvironment results in upregulation of immunoinhibitory programmed cell death-1 (PD-1) marker, alters homeostatic proliferation and differentiation pathways of T-cell subsets in an animal model of chronic viral infection 20 , 21 . In this present study, we explored the effect of METH on cell cycle regulators and their role in suppression of T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%